2022
DOI: 10.1038/s41467-022-35375-2
|View full text |Cite
|
Sign up to set email alerts
|

Structural insights into p300 regulation and acetylation-dependent genome organisation

Abstract: Histone modifications are deposited by chromatin modifying enzymes and read out by proteins that recognize the modified state. BRD4-NUT is an oncogenic fusion protein of the acetyl lysine reader BRD4 that binds to the acetylase p300 and enables formation of long-range intra- and interchromosomal interactions. We here examine how acetylation reading and writing enable formation of such interactions. We show that NUT contains an acidic transcriptional activation domain that binds to the TAZ2 domain of p300. We u… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 175 publications
2
19
0
Order By: Relevance
“…Consistent with the notion that CBP/p300 play important roles in Aire targeting to active loci, both degrader dCBP-1 and catalytic inhibitor A-485 impaired Aire binding to SEs (Figures 3F and 3G). This suggests that Aire may preferentially home in on the catalytically active form of CBP/p300 that often form clusters and accumulate at active genetic loci 2,59,60 .…”
Section: Resultsmentioning
confidence: 99%
“…Consistent with the notion that CBP/p300 play important roles in Aire targeting to active loci, both degrader dCBP-1 and catalytic inhibitor A-485 impaired Aire binding to SEs (Figures 3F and 3G). This suggests that Aire may preferentially home in on the catalytically active form of CBP/p300 that often form clusters and accumulate at active genetic loci 2,59,60 .…”
Section: Resultsmentioning
confidence: 99%
“…During the course of this study, two studies reported that the BRD4-NUT fusion protein contains two TADs in NUT that bind to TAZ2, and the TAD-TAZ interaction triggers allosteric activation of p300 and acetylation-driven liquid-like condensation on chromatin 35,36 . Ibrahim et al showed that in vitro, the NUT TADs stimulate autoacetylation of the p300s fragment (aa324-2094), but not a shorter p300 fragment (aa1048-1664) 36 .…”
Section: Cells With Taz2 Truncations Are Vulnerable To Hdac Inhibitorsmentioning
confidence: 97%
“…Somatic expression of NUTM1 protein is problematic because its normal function is to hyperacetylate histones for their removal during spermatogenesis (Shiota et al 2018, Rousseaux et al 2022). Thus, it is a powerful attractor and facilitator of the p300/CBP histone acetyltransferases (Wang and You 2015, Ibrahim et al 2022, Yu et al 2023.…”
Section: Introductionmentioning
confidence: 99%